Effect of age, female mating status and density on the banana weevil response to aggregation pheromone - Tinzaara, William; Gold, Cliford S.; Dicke, M.; Huis, A. van; Ragama, P.E. (African Journals Online, 2011)
The banana ( Musa spp.) weevil ( Cosmopolites sordidus (Germar) (Coleoptera: Curculionidae) is a major pest in East Africa causing yield losses of up to 14 metric tonnes per hectare annually. Laboratory and field experiments were conducted to determine whether the response of the banana weevil, Cosmopolites sordidus (Germar) (Coleoptera: Curculionidae) to its aggregation pheromone was influenced by age, female mating status and weevil density. Laboratory bioassays were conducted using a double pitfall olfactometer, while a bucket pitfall trap was used in field experiments. There was no significant (P>0.05) difference in response to pheromone between immature and mature weevils (males and females) in laboratory bioassays. Forty-day-old weevils had a stronger response to the pheromone than 10-day-old ones under field conditions. The response of unmated weevils to the pheromone was stronger than that of mated weevils, both in the laboratory and field. The percentage of unmated and mated weevils recaptured from 0 and 3 m were similar but significantly different from 6 m way from the pheromone baited trap. The response of the weevils to the pheromone was not significantly (P>0.05) influenced by its previous density.